The Effectiveness of Rational Emotive Behavior Therapy Group Counseling in Reducing Cheating Behaviors - Ariadi Nugraha; Sri Hartini (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2021)
This study aims to reduce cheating behavior in students by using Rational Emotive Behavior Therapy group counseling. This research is a pre-experimental design research, namely One Group Pretest and Posttest Design. The subjects of this study were ten third semester students of the Guidance and Counseling study program at Ahmad Dahlan University, ten students were taken using purpsoive sampling technique. The instrument used in this research is the cheating behavior scale. Analysis of the data used in this study by using the effectiveness test with the t-test formula. The results of the study showed that group counseling with the Rational Emotive Behavior Therapy approach was proven effective in reducing cheating behavior in Guidance and Counseling students at Ahmad Dahlan University. Most of the cheating behavior carried out by students in the category of social passive and cheating behavior in students is mostly based on a lack of confidence in their abilities. The results of this study can be used as an alternative counseling strategy for counselors in universities to reduce cheating behavior in students.